Systematic Literature Review: Peran Filsafat Ilmu Dalam Kehidupan Sehari-Hari - Delisi, Ferna (Journal of Innovation in Teaching and Instructional Media, 2025)
The aim of this paper is to discover and analyze how important the philosophy of science is in everyday life. The method used in this research is Systematic Literature Review, the material used is 15 articles journal taken from Google Scholar published during the last 5 years. It is hoped that this research can help understand and see clearly the purpose of the knowledge that is held. How we can develop critical thinking that can help evaluate information and arguments rationally. Encouraging healthy skepticism is proven by not easily believing without sufficient evidence. Bridging science with ethics is reflected in integrating knowledge with moral and social values. Increasing adaptability in the form of accepting changes and developments in science. Increase social sensitivity so that you can understand the social, cultural and historical context behind science, so, you can make wise decisions by considering evidence from various points of view, as well as strengthening information literacy so that you can differentiate facts from opinion or misinformation.